The Influence of Hedonic Shopping Value, Price Discount, and Store Atmosphere Against Impulse Buying Dayumart Consumers Sumatra Padang - Pratama, Geza Syafti; Wahyudi, Harry (ADPEBI, 2024)
This study aims to find out how the influence of hedonic shopping value, price discount, and store atmosphere on impulse buying in Dayumart Sumatra Ulak Karang Padang consumers. The sampling technique uses a purposive sampling technique, using the Lemeshow formula so that a sample of 96 people was obtained. The F test is known that the value of 18.038 > f table is 3.09 with a significance value of 0.000 or (0.000 < 0.05). So in this study, the independent variables together affect the dependent variables. The determination coefficient was obtained with a result of 0.370. This means that the variables of hedonic shopping value, price discount, and store atmosphere can explain the impulse buying variables in 37% of Dayumart Sumatra Ulak Karang Padang consumers. The remaining 63% was explained by other variables that were not observed in this study.